Beyond Zooming there: Understanding nonverbal interaction online - Park, So Yeon; Whiting, Mark E. (2020)
ABSTRACT Social distancing has shifted us towards virtual platforms, inducing us to engage in video-conferencing at overwhelming rates. Yet, recognizing subtle nonverbal signals in these contexts — being aware of how our actions are presented, and building empathy through video-conferencing — proves challenging as ambiguity increases. We show evidence that unexplained nonverbal actions in online platforms evoke more negative affect than those same actions when their reason is known. Further, through pilots we show that unmanaged nonverbal interaction in video-conferencing can evoke hostile attribution bias. We posit that surfacing rationales behind nonverbal actions will increase empathy and richness in video-conferencing and other online interactions crucial to the future of work. Widespread increases in remote work has amplified the prevalence of these challenges, motivating further study of nonverbal actions online and their consideration in CSCW system designs. Keywords nonverbal interaction, empathy, teleconference, video chat ABOUT THE AUTHOR/S SO YEON PARK Stanford University syjpark@stanford.edu So Yeon (syjpark.com) is a PhD candidate at Stanford. She investigates design affordances for collaborative online systems with the belief that design can shape collaboration behaviors to help people work better together. MARK E. WHITING University of Pennsylvania markew@seas.upenn.edu Mark (whiting.me) is a postdoc with Duncan Watts in both CIS in Engineering, OID at Wharton at U Penn. He holds degrees in Industrial Design from RMIT and KAIST, a PhD in Mechanical Engineering from CMU, and a previous postdoc in HCI from Stanford. New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).